PHYSICIANS AND PHARMACISTS’ EXPERIENCES, AWARENESS, AND BARRIERS IN PROVIDING SAFE PRESCRIPTIONS FOR GERIATRIC PATIENTS: A CROSS-SECTIONAL SURVEY - Laksmi Maharani; Fita Rahmawati; Zullies Ikawati; Mustofa (Universitas Airlangga, 2026)
Introduction: Potentially inappropriate medications (PIMs) are frequently prescribed to older adults, increasing the risk of adverse drug events. Physicians and pharmacists play key roles in minimizing PIM use through rational prescribing and medication review. However, awareness and experience with PIM screening tools among healthcare professionals in Indonesia remain limited. This study aimed to assess physicians' and pharmacists' awareness, experiences, and barriers to rational prescribing for the elderly, particularly regarding the avoidance of PIMs, in Indonesia. Methods: A cross-sectional survey was conducted among general practitioners (GPs), internists, neurologists, geriatricians, and hospital pharmacists at two teaching hospitals in Yogyakarta, Indonesia. A self-administered, valid, and reliable questionnaire was used, and the data obtained were analyzed using Mann-Whitney and Spearman Correlation. Results: Among 91 participants, more than 50% of pharmacists and physicians have no experience in using explicit PIM criteria. Most pharmacists (58.33%) and physicians (58.18%) demonstrated high to very high awareness in avoiding PIMs as presented in the questionnaire scenario. There was a correlation between physicians' and pharmacists’ awareness of PIM and their duration of practice (p<0.05). The main barriers identified by pharmacists were polypharmacy, drug intolerance, and medication costs, whereas physicians highlighted potential drug interactions, polypharmacy, and reimbursement policies under the national health insurance (NHI) scheme. Conclusion: In geriatric patient care, closely related to polypharmacy, PIMs that cannot be avoided require strict monitoring to ensure patient safety.